Maggot therapy and monstrosity: the grotesque in Margaret Atwood's The Year of the Flood - Ong, Li Yuan; Ali Termizi, Arbaayah; Moghadam, Nahid Shahbazi; Talif, Rosli (Universiti Putra Malaysia Press, 2018)
Speculative fiction is able to foresee the changes of the environment and social strata via imitation of future society (Gough, 2003; Otto, 2012). With the same intention, Margaret Atwood makes use of an alternative natural medication, maggot therapy, as an important recuperative method to cure physical lesions and injuries in The Year of the Flood (2009). Historically, although once a common practice among healers of antiquity, maggot therapy has since been discarded from medical context, partly due to its carnivorous and parasitic nature. The present paper intends to discuss the implication of this kind of natural therapy and its sense of monstrosity and grotesqueness as presented in Atwood's novel. In using this therapy as motif, the novel illustrates the grotesque through exaggeration and gory and monstrous features, which lead not only the characters but also the readers to experience disorientation due to the unfamiliar state of savagery. With a focus on relevant theories of the grotesque, the study aims to highlight how the monstrosity inherent in maggot therapy renders the grotesque in this novel, that is, by juxtaposing savagery and culture and evoking repulsion and attraction.